Computer design and modeling of energy systems in the educational process - Bahach, Ruslan; Latvynskyi, Vladislav; Plakhtii, Oleksandr; Filipieva, Maryna; Багач, Руслан; Латвінський, Владислав; Плахтій, Олександр; Філіп’єва, Марина (Харківський національний автомобільно-дорожній університет, 2025)
The article highlights the role of computer modeling in the training of energy specialists. Software complexes (MATLAB, ANSYS, ETAP, PSCAD) for the analysis and optimization of energy systems are described. Examples of application are given, in particular, the design of solar and charging stations. The advantages of modeling are determined: resource saving, accuracy of analysis. The importance of digital technologies in the training of specialists in sustainable development is emphasized. Goal. Analysis of the importance of computer design and modeling in the training of energy specialists, studying modern software packages, and evaluating their impact on the effectiveness of the educational process. Methodology. The study is based on the analysis of scientific sources, comparison of programs (MATLAB, ANSYS, ETAP, PSCAD), review of cases and experimental modeling of power systems. The impact of digital technologies on the formation of students' professional skills is assessed. Results. The effectiveness of computer modeling in the training of energy professionals was confirmed. Software packages (MATLAB, ANSYS, ETAP, PSCAD, HOMER Pro, Energy Plus) for modeling and optimizing energy systems were analyzed. The advantages of digital technologies were identified: resource saving, risk-free testing, accuracy of analysis. Cases of solar power plant design, network analysis, cooling optimization and charging stations were considered. Integrating modeling promotes the development of critical thinking and analytical skills. Originality. The study highlights the importance of computer modeling in the education of energy professionals. The use of modern programs (MATLAB, ANSYS, ETAP, PSCAD) in the educational process is analyzed. Their role in optimizing energy systems and developing critical skills is shown. The importance of modeling for innovation and interdisciplinary collaboration is emphasized. The integration of models strengthens theoretical knowledge and practical skills. Practical value. The results of the study contribute to the improvement of the training of power engineers. The integration of modeling (MATLAB, ANSYS, ETAP, PSCAD) improves the quality of training without significant equipment. The optimization of courses through interactive tasks and projects is useful for education, science and consulting.
Комп'ютерне проєктування та моделювання енергетичних систем у навчальному процесі
Keywords: Computer modeling; energy systems; software packages; MATLAB; ANSYS; ETAP; PSCAD; Комп’ютерне моделювання; енергетичні системи; програмні комплекси; MATLAB; ANSYS; ETAP; PSCAD; 621.311; 10.30977/VEIT.2025.27.0.4